English Instructional Model Used by the Lecturers in Preparation to Teach Speaking Skill at Makassar Muhammadiyah University - Fitrisyam Harming; Andi Tenri Ampa; Syamsiarna Nappu (ELT Worldwide: Journal of English Language Teaching, 2022)
The main objective of this research is to discover the instructional design model (IDM) that used by the English lecturers in preparation to teach speaking skill specifically in English Department of Makassar Muhammadiyah University. The models are ADDIE, Kemp, and ASSURE model. In addition, the efficiency of the instructional design model application by lecturers is also demonstrated in this research by the students' speaking skill achievement data. This research used mix method design. The subject of the research were 1 lecturer and 29 students from English Department of Makassar Muhammadiyah University. The instruments used interview and questionnaire (for lecturer) and test as the instrument (for students’ speaking achievement). Result of the research demonstrated that the ADDIE Model was implemented 91% of the stages, then Kemp and ASSURE models were implemented 100%. Finally, the lecturer complete 96% of the stages from the three IDM models. Then, students' speaking skill achievement presents that 10.3% of students were in the very good category, 34.4% were in the good category, 48.3% were in the average category, and 0% of students were in the poor category. So, it can be concluded from the research that when the instructional design model was effectively implemented, students' speaking skills improved significantly. This is evidenced by the absence of students who were in the poor category.